Power, Food and Agriculture: Implications for Farmers, Consumers and Communities - Mary K. Hendrickson; Philip H. Howard; Douglas H. Constance (The Bichler and Nitzan Archives, 2017)
One of the most pressing concerns about the industrialization of agriculture and food is the consolidation and concentration of markets for agricultural inputs, agricultural commodities food processing and groceries. In essence a small minority of actors globally exercise great control over food system decisions. This means that because of increased consolidation of these markets globally – from the United States to China to Brazil, from South Africa to the United Kingdom – the vast majority of farmers, consumers and communities are left out of key decisions about how we farm and what we eat. Transnational agrifood firms are motivated by profits and power in the marketplace, leaving other social, economic and ecological goals behind. This creates an agroecological crisis in the face of climate uncertainty but one that is rooted in social and economic organization. In this chapter we detail the current economic organization of agriculture, and briefly describe its negative impacts on farmers, communities and ecology. We conclude by articulating stories of farmer-led resistance that imagine a new food system.
Keywords: 330; agriculture; capital as power; farmers; food; power